SYNTHESIS OF STRUCTURES OF OPERATING DEVICES IMPLEMENTATION CRYPTOGRAPHIC ALGORITHMS IPSEC OF OPTIMIZED FOR MEDIA PACKAGES PROCESSIN - Korkishko, Tymoor; Shevchuk, Ruslan (International Journal of Computing, 2014)
In the paper the operating device of IPSec protocol optimized for treatment media of packages is investigated. Analytical expressions which describe time of media packages processing depending on the parameters of operating device structure are offered, the mathematical model of operating device of IPSec processor is developed. On the basis of mathematical model, with the purpose of reduction of delay and jitter, which rise up during the generation of media package, software is developed for optimization of structures descriptions of processor IPSec operating device. The row of the optimized structures of operating device is got for different services of given IPSec treatment at different technological descriptions of component base. The analysis of results allowed to set that in most cases, the least time of treatment media of packages is observed at iterative and iterative-conveyer realization of IPSec operating device.